2017
DOI: 10.1016/j.ijheh.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Associations between long-term exposure to air pollution, glycosylated hemoglobin and diabetes

Abstract: BACKGROUND Air pollution exposures have been shown to adversely impact health through a number of biological pathways associated with glucose metabolism. However, few studies have evaluated the associations between air pollution and glycosylated hemoglobin (HbA1c) levels. Further, no studies have evaluated these associations in US populations or investigated whether associations differ in diabetic as compared to non-diabetic populations. To address this knowledge gap, we investigated the associations between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 30 publications
(63 reference statements)
4
55
0
4
Order By: Relevance
“…Several studies provide strong evidence that shows that increases in ambient PM levels lead to increased incidence rates of metabolic diseases, which include but are not limited to diabetes and dyslipidaemia [19][20][21]. Furthermore, another study by Yitshak Sade et al suggested that increases in the levels of FBG, glycosylated haemoglobin, and LDL-C are associated with increase in PM 10 and PM 2.5 concentrations at 3-month intervals from exposure [22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies provide strong evidence that shows that increases in ambient PM levels lead to increased incidence rates of metabolic diseases, which include but are not limited to diabetes and dyslipidaemia [19][20][21]. Furthermore, another study by Yitshak Sade et al suggested that increases in the levels of FBG, glycosylated haemoglobin, and LDL-C are associated with increase in PM 10 and PM 2.5 concentrations at 3-month intervals from exposure [22].…”
Section: Discussionmentioning
confidence: 99%
“…A cross‐sectional study in China observed an elevated PR = 1.14 for diabetes as well as a positive association with HbA1c (a mean increase in 0.08%; 95% CI, 0.06‐0.10) per IQR increase in ambient PM 2.5 (41.1 μg/m 3 ) . Other studies evaluating PM 10 in ambient air have also reported a positive association between air pollution and diabetes . We use PRs from Poisson regression and ORs from logistic regression to report our results on prediabetes/diabetes prevalence as both methods have been used when analyzing and interpreting binary outcomes from cross‐sectional data.…”
Section: Discussionmentioning
confidence: 99%
“…20 Other studies evaluating PM 10 in ambient air have also reported a positive association between air pollution and diabetes. [21][22][23] We use PRs from Poisson regression and ORs from logistic regression to report our results on prediabetes/diabetes prevalence as both methods have been used when analyzing and interpreting binary outcomes from cross-sectional data. The PR is a conservative measure and may be easier to interpret, while the TA B L E 2 24-h mean air pollution data for the total population and by stove type among Honduran women using traditional and Justa stoves OR may overestimate associations, particularly when the outcome is not rare, but has been more widely used in previous studies, and therefore, allows for greater comparability.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 9 literature [11,[13][14]17,19,[21][22][23]29] including NO 2 as an exposure factor. Two articles had both type 1 and 2 diabetes as outcomes,7 articles had type 2 diabetes as outcomes.…”
Section: No 2 and Risk Of Diabetesmentioning
confidence: 99%